2015
DOI: 10.3389/fpls.2015.00794
|View full text |Cite
|
Sign up to set email alerts
|

Role of Large Cabbage White butterfly male-derived compounds in elicitation of direct and indirect egg-killing defenses in the black mustard

Abstract: To successfully exert defenses against herbivores and pathogens plants need to recognize reliable cues produced by their attackers. Up to now, few elicitors associated with herbivorous insects have been identified. We have previously shown that accessory reproductive gland secretions associated with eggs of Cabbage White butterflies (Pieris spp.) induce chemical changes in Brussels sprouts plants recruiting egg-killing parasitoids. Only secretions of mated female butterflies contain minute amounts of male-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Mechanical injury is well known for eliciting repair and defense responses (Mithöfer et al, 2005;Duran-Flores and Heil, 2016). Second, plants may respond to spider mite egg-deposition as has been demonstrated for the eggs of dipteran (Hilker et al, 2002;Bittner et al, 2017), lepidopteran (Fatouros et al, 2015), and coleopteran (Doss et al, 2000) insects, and was shown to sometimes benefit the insect (Hilker and Fatouros, 2015;Hilker and Fatouros, 2016). Third, plants may respond to spider mite secretions such as silk (Grbic et al, 2011;Dogȃn et al, 2017), feces (Santamaria et al, 2015), and especially the saliva they inject into host cells during feeding, reminiscent of herbivorous insects (Howe and Jander, 2008;Maffei et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical injury is well known for eliciting repair and defense responses (Mithöfer et al, 2005;Duran-Flores and Heil, 2016). Second, plants may respond to spider mite egg-deposition as has been demonstrated for the eggs of dipteran (Hilker et al, 2002;Bittner et al, 2017), lepidopteran (Fatouros et al, 2015), and coleopteran (Doss et al, 2000) insects, and was shown to sometimes benefit the insect (Hilker and Fatouros, 2015;Hilker and Fatouros, 2016). Third, plants may respond to spider mite secretions such as silk (Grbic et al, 2011;Dogȃn et al, 2017), feces (Santamaria et al, 2015), and especially the saliva they inject into host cells during feeding, reminiscent of herbivorous insects (Howe and Jander, 2008;Maffei et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“… 28 30 . PR genes are also more strongly expressed in response to eggs in several plant species 12 , 15 , 31 , 32 . We found strong conformable up-regulation of SA-related GS in response to eggs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Traces of antiaphrodisiacs were detected into female accessory glands and, when in contact with brassicaceous plants, these compounds induce wax epicuticular changes that arrest Trichogramma egg parasitoids (Fatouros et al, 2009). However, application of antiaphrodisiacs do not fully mimic egg deposition in terms of plant defences, as these compounds do not trigger OIPVs attracting Trichogramma parasitoids (Fatouros et al, 2015). This is similar to our findings, as T. basalis attraction could not be restored when secretions from N. viridula male accessory glands were applied to V. faba plants highlighting the intricacy of plant responses to insect egg deposition.…”
Section: Discussionmentioning
confidence: 99%